The importance of agricultural marketing in stimulating plant production in the Fezzan region (Journal of Pure & Applied Sciences, 2023)
This study aimed to shed light on the role of agricultural marketing in improving agricultural production and to identify marketing difficulties in the study area. The research is of great importance because it discusses a problem related to food security by addressing the marketing aspect, which is a complementary part of the established agricultural policies. The study concluded that efforts must be made to solve the various marketing problems, such as transportation, storage and prices, to transfer agricultural production from the Fezzan region to all regions of Libya. The wise intervention of the state to work out solutions to the problems of roads and electricity and provide incentives and loans to investors in the field of marketing, it may be an appropriate solution to stimulate marketing activity in the region. It is also necessary to use modern methods of marketing, including electronic marketing, as well as agricultural air transport of agricultural crops from the regions of the region to most of the regions of Libya. The state has put in place different agricultural policies related to food security, and production has developed and varieties have diversified, but the quantities of local production do not cover the different and growing population needs. Agricultural production improved in the Fezzan region and diversified from vegetables, fruits and grains, but there is no reflection of this improvement on the self-sufficiency rate of agricultural crops in Libya.